Effects of Exercise Training and IL-6 Receptor Blockade on Gastric Emptying and GLP-1 Secretion in Obese Humans: Secondary Analyses From a Double Blind Randomized Clinical Trial - Lehrskov, Louise Lang; Christensen, Regitse Højgaard; Wedell-Neergaard, Anne-Sophie; Legaard, Grit Elster; Dorph, Emma; Larsen, Monica Korsager; Henneberg, Marie; Launbo, Natja; Fagerlind, Sabrina Ravn; Seide, Sidsel Kofoed; Nymand, Stine; Ball, Maria; et al. (Frontiers in Physiology, 2019)
Background: Interleukin-6 (IL-6) is released from skeletal muscle during exercise and systemic IL-6 levels therefore increase acutely in response to a single bout of exercise. We recently showed that an acute increase in IL-6 delayed gastric emptying rate and improved postprandial glycemia. Here we investigate whether repeated increases in IL-6, induced by exercise training, influence gastric emptying rate and moreover if IL-6 is required for exercise-induced adaptations in glycemic control including secretion of glucagon and glucagon-like peptide-1 (GLP-1). Methods: 52 abdominally obese non-diabetic men and women were randomly assigned into four groups performing 12 weeks of endurance exercise or no exercise with or without IL-6 receptor blockade (tocilizumab). The primary endpoint was change in gastric emptying rate in response to the intervention and other endpoints included changes in glycemic control, glucagon and GLP-1 secretion. Results: There was no change in gastric emptying rate in any of the four groups following the intervention and comparing differences in change between groups also revealed no difference. Postprandial glucose remained unchanged in all groups but the exercise + tocilizumab group, which improved postprandial glucose in response to the intervention. The area under the curve for meal-stimulated glucagon, active and total GLP-1 increased in response to IL-6 receptor blockade, this effect was independent of exercise. Conclusion: Exercise training and long-term IL-6 receptor blockade did not change gastric emptying rates in obese humans. IL-6 receptor blockade increased glucagon and GLP-1 secretion and implicate IL-6 in the regulation of the human alpha and L cells.